ANALISIS LAPORAN KEUANGAN PT. GATARI SEBAGAI DASAR PERTIMBANGAN PEMBERIAN KREDIT MODAL KERJA PADA PT.BANK DKI - Zannati, Rachma; Fitriana, Nur (Economic Faculty, Attahiriyah Islamic University, 2016)
This study aims to determine (a) measure the feasibility assessment takes into account the provision of working capital credit for PT.Gatari as additional capital by comparing financial ratios (liquidity, solvency, profitability, and activity) for the period 2012-2015, and (b) measure the credit granting considerations on PT. Gatari according to standard financing considerations on PT. Bank DKI. This research is a descriptive method with the quantitative approach to PT. Gatari financial statements from its inception until today. The research sample is PT. Gatari financial statements in 2013, 2014 and 2015. The study shows that (a) the measurement of financial feasibility assessment showed good results because the calculation of the ratio is almost entirely according to the standard financial ratios applicable at PT. Bank DKI and (b) the measurement of supporting aspects of credit is good enough as a basis for credit supply PT. Bank DKI. Keywords: Liquidity Ratios, Solvency Ratios, Activity Ratios, Profitability Ratios, Working Capital Loan